Determining the Effect of the Picture Archiving and Communication System (PACS) on Different Dimensions of Users’ Work - Mahdieh Montazeri; Reza Khajouei (Radiology Research and Practice)
The impact of the picture archiving and communication system (PACS) on healthcare costs, information access, image quality, and user workflow has been well studied. However, there is insufficient evidence on the effect of this system on different dimensions of the users’ work. The objective of this study was to evaluate the impact of the PACS on different dimensions of users’ work (external communication, service quality, user intention to use the PACS, daily routine, and complaints on users) and to compare the opinions of different groups of users about the PACS. This study was performed on the PACS users (n = 72) at Kerman University of Medical Sciences, including radiologists, radiology staff, ward heads, and physicians. Data were collected using a questionnaire consisting of two parts: demographic information of the participants and 5-point Likert scale questions concerning the five dimensions of users’ work. Data were analyzed using descriptive statistics, ANOVA, and Pearson’s correlation coefficient statistical tests. The mean of scores given by the PACS users was 4.31 ± 0.86 for external communication, 4.18 ± 0.96 for user intention to use the PACS, 3.91 ± 0.7 for service quality, 3.16 ± 0.56 for daily routine, and 3.08 ± 1.05 for complaints on users. Radiologists and radiology staff had a more positive opinion about the PACS than other clinicians such as physicians (P<0.01, CI = 95%). Factors such as user age (P<0.01, CI = 95%), job (P<0.001, CI = 95%), work experience (P<0.001, CI = 95%), and PACS training method (P=0.037, CI = 95%) were related to the impact of the PACS on different dimensions of users’ work. This study showed that the PACS has a positive effect on different dimensions of users’ work, especially on external communication, user intention to use the system, and service quality. It is recommended to implement PACSs in medical centers to support users’ work and to maintain and strengthen the capabilities and functions of radiology departments.